Benefits of six week and personalized dosing of pembrolizumab considering ongoing delta variant surge - Iqbal, Arham; Abbasi, Zaeem Ahmed; Naeem, Fahad (Journal of the Pakistan Medical Association, 2022)
Dear sir, The on-going discussion on fixed dosing or personalized dosing of pembrolizumab has created great chaos among the patients of metastatic non-small cell lung cancer (NSCLC). Below mentioned are few points in this regard, Delta variant has affected economies of Asian countries in multiple ways. Personalized and six week dosing of pembrolizumab can be beneficial in this regard. A study conducted by DANIAL A. GOLDSTEIN and co-authors, compared fixed dosing of pembrolizumab with personalized dosing. They have concluded the result that personalized dosing can save upto 24.0% of annual savings in US that is equal to 0.825 billion dollar [1]. These results are supported by another study in which Q6W dosing of pembrolizumab is compared with Q3W dosing. The study states that 400 mg Q6W dosing of pembrolizumab leads to results that are very similar to 200mg Q3W dosing regimen [2]. Another study proposed weight based as well as six weeks dosing of pembrolizumab for the ease of cancer patients [3]. As pembrolizumab is approved for patients with stage III resected melanoma therefore delaying its therapy may have similar effects on overall survival [4]. Keeping all these point in view we would like to suggest that it would be better if doctors from now onwards suggest Q6W dosing of pembrolizumab instead of Q3W dosing as well as personalized dosing should be promoted as compared to fixed dosing as this well help in lowering down the financial as well as health burden on patients with metastatic non-small cell lung cancer (NSCLC). Continue...